2014
DOI: 10.1007/s00167-014-3195-y
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical factors influencing patellar tracking in the unstable patellofemoral joint

Abstract: Diagnostic study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 37 publications
4
86
0
3
Order By: Relevance
“…The subjects with PFP demonstrated a greater magnitude compared with the subjects without PFP at all knee flexion angles with the largest difference between groups was evident at full extension. The subjects with and without PFP demonstrated an overall pattern of increasing lateral tilt as the knee extended, which was consistent with other authors (Biyani et al 2014;Teng et al 2014). …”
Section: Predictors Of Patellofemoral Pain Applying Full Weight Bearisupporting
confidence: 92%
“…The subjects with PFP demonstrated a greater magnitude compared with the subjects without PFP at all knee flexion angles with the largest difference between groups was evident at full extension. The subjects with and without PFP demonstrated an overall pattern of increasing lateral tilt as the knee extended, which was consistent with other authors (Biyani et al 2014;Teng et al 2014). …”
Section: Predictors Of Patellofemoral Pain Applying Full Weight Bearisupporting
confidence: 92%
“…The affect ed knee demonstrated greater patellar displacement at low flexion angles. The average bisect offset index in the painful knee was 7% at full extension, which is in agreement with the other authors, who investigated affected and pain free knees in different individuals (12,13). The greatest bisect offset index in the painful knee at full extension was 92%, which might be influenced by weak passive medial stabilizers, namely the medial patellar retinaculum.…”
Section: Discussionsupporting
confidence: 91%
“…Our results confirmed the data of other investigators who have reported greater bisect offset index for the affected knee as compared to the pain-free knee in kinematic weight-bearing MRI examinations in different individuals (11,12). Both knees have demonstrated a similar increasing bisect offset from 50° to 30° of flexion, while diverging at low angles of flexion, especially at full extension.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…3,4,11,12,15,16 Despite its extensive use, in cases where the TT-TG distance is <20 mm, it may not be able to explain other cases seen to have instability. 17,18 In the current study, it was attempted to answer the following questions: (1) Are metric parameters alone sufficient in the evaluation of patellar instability? (2) Can angular parameters be defined which will reveal the rotational movement of the tuberositas tibia on the tibia shaft, additional to the metric parameters?…”
Section: Introductionmentioning
confidence: 99%